Al-anodizing waste as a supplementary cementitious material for 3D-printed Portland cement - Jairon Gomes da Silveira Júnior; Rafael Dors Sakata; Lucas Onghero; Paulo Ricardo de Matos; Erich David Rodríguez; Lisandro Simão; Antonio Pedro Novaes de Oliveira; Ruan Carlos de Araújo Moura; Carlos Eduardo Maduro de Campos; José Renato de Castro Pessôa; Marcelo Tramontin Souza (Waste Management Bulletin)
This study investigates the use of Al-anodizing waste (AAW), a byproduct of the anodizing process for aluminum and its alloys, in cement composites designed for 3D printing applications. For cementitious materials to be suitable for 3D printing, they must maintain adequate stability to support overlapping layers while also exhibiting sufficient flowability and open time for effective pumping. The incorporation of AAW aims to improve the rheological properties of these mixtures, enhancing both their open time and buildability. To evaluate the potential of AAW in 3D printing cement composites, a comprehensive approach was adopted. This included rheological analysis, flow table testing, investigations into buildability, and assessments of mechanical performance. Additional techniques, such as isothermal calorimetry and in situ X-ray diffraction, were employed to examine the effect of AAW on the hydration kinetics of cement pastes. The findings highlighted several advantages of incorporating AAW into cement-based formulations, such as improved buildability, quick adjustments in rheological properties, prolonged open times, enhanced mechanical performance, cost-effectiveness, and increased sustainability by transforming a commonly discarded material into a valuable resource for civil construction.